Ramping‐Up Electrolyser Manufacturing for the Green Hydrogen Transition: A Planning Approach for Scalable Factory Concepts - Michael Riesener; Esben Schukat; Niklas Schäfer; Nils Lehde genannt Kettler; Sebastian Junglas (Electrochemical Science Advances)
ABSTRACT In pursuit of more sustainable energy systems, green hydrogen supports renewable energy supply and enables flexible energy storage. To achieve both nationally and globally set goals of the green hydrogen transition, affordable hydrogen electrolysers need to be available. However, only small‐scale production facilities have yet been established. Manufacturing companies are struggling to scale up production capacities to meet the rising yet fluctuating and uncertain market demands. However, existing factory planning methods do not satisfy the associated requirements. Therefore, we introduce a planning approach for developing scalable factory concepts that enable industrial high‐scale production. The proposed planning approach is structured around a five‐step procedure model that outlines the necessary planning tasks, both for the production system and IT system design. To automate the planning tasks, we describe a prototype implementation, which we apply to an electrolyser manufacturing company's use case in the series production of electrolysers in the gigawatt range (SEGIWA) research project on scalable electrolyser manufacturing. The project's technological focus is proton exchange membrane (PEM) electrolysis. Various planning scenarios are derived and validated by digital tools with 3D factory models. Finally, we discuss the advantages and shortcomings of the planning approach, which provides a framework for adapting production systems to the challenges posed by new technologies and dynamic market conditions. Thus, our contribution empowers manufacturers to design industrial production systems for scaling up electrolyser manufacturing, thereby contributing practically to the green hydrogen transition.